PEMIKIRAN GEORGE POLYA TENTANG PEMECAHAN MASALAH - Dianti Purba; Zulfadli Nasution; Roslian Lubis (JURNAL MathEdu (Mathematic Education Journal), 2021)
The background of this research is Covid 19 pandemic that it made the learning online. This case is a problem because students are not able to master the topic that given by teachers especially in mathematics learning that need problem solving. George Polya had given a solution to overcome this problem in his book entitle “How to solve it”. The thinking will be described in this research by approach library research. The informants of the research are bapak Muhammad Syahril Harahap and ibu Rahmatika Elindra. They are the lectures of mathematics department of IPTS. The research result is 1) thinking of George Polya is an effort to look for an overcome from a difficulty to get a purpose that it is not able to achieved soon and 2) there are 4 steps of problem solving which included a) understand the problem, b) planning completion the problem, c) conducting completion the problem, and d) correction the result again . Based on the explanation above, it’s concluded thinking of George Polya can apply in learning mathematics in Covid 19 pandemic.